Functional outcomes of outpatient balance training following total knee replacement in patients with knee osteoarthritis: a randomized controlled trial. (September 2015) - Liao, Chun-De; Lin, Li-Fong; Huang, Yi-Ching; Huang, Shih-Wei; Chou, Lin-Chuan; Liou, Tsan-Hon
Objective: To evaluate whether balance training after total knee replacement surgery improves functional outcomes and to determine whether postoperative balance is associated with mobility. Design: A prospective intervention study and randomized controlled trial with an intention-to-treat analysis. Setting: The rehabilitation center of a university-based teaching hospital. Participants: A total of 130 patients with knee osteoarthritis who had undergone total knee replacement surgery were recruited to attend an outpatient rehabilitation program. They were randomly allocated to additional balance rehabilitation and functional rehabilitation groups. Interventions: During the eight-week outpatient rehabilitation program, both groups received general functional training. Patients in the balance rehabilitation group received an additional balance-based rehabilitation program. Primary outcome measures: The functional reach test, single-leg stance test, 10-m walk test, Timed Up and Go Test, timed chair-stand test, stair-climb test, and Western Ontario and McMaster Universities Osteoarthritis Index were measured at baseline, eight weeks (T1 ), and 32 weeks (T2 ). Results: The balance rehabilitation group patients demonstrated significant improvement in the results of the functional reach test at T1 (37.6 ±7.8 cm) and T2 (39.3 ±9.7 cm) compared with the baseline assessment (11.5 ±2.9 cm) and Timed Up and Go Test at T1 (8.9 ±1.2 seconds) and T2 (8.0 ±1.9 seconds) compared with the baseline assessment (12.5 ±1.8 seconds). Moreover, the balance rehabilitation group patients exhibited significantly greater improvements in balance and mobility than did the functional rehabilitation group patients (all P < 0.001). Furthermore, improved balance was significantly associated with improved mobility at T2 . Conclusion: Postoperative outpatient rehabilitation with balance training improves the balance, mobility, and functional outcomes in patients with knee osteoarthritis after total knee replacement.